2022
DOI: 10.1007/s11042-022-12802-6
|View full text |Cite
|
Sign up to set email alerts
|

You can try without visiting: a comprehensive survey on virtually try-on outfits

Abstract: Since the last years and until now, technology has made fast progress for many industries, in particularly, garment industry which aims to follow consumer desires and demands. One of these demands is to fit clothes before purchasing them on-line. Therefore, many research works have been focused on how to develop an intelligent apparel industry to ensure the online shopping experience. Image-based virtual try-on is among the most potential approach of virtual fitting that tries on target clothes into customer's… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…In this paper, our emphasis will be on the deep learning-based models that have gained more popularity within the research community and shown greater promise in applications. Interested readers can refer to [27], [59], and [61] for further details regarding the 3D virtual try-on models.…”
Section: A Physics-based Virtual Try-onmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, our emphasis will be on the deep learning-based models that have gained more popularity within the research community and shown greater promise in applications. Interested readers can refer to [27], [59], and [61] for further details regarding the 3D virtual try-on models.…”
Section: A Physics-based Virtual Try-onmentioning
confidence: 99%
“…These outcomes include increased visitor numbers, longer time spent on the site, higher spending, and greater sales, as well as an increase in the conversion rate of customers [101]. By employing virtual try-on models, it is observed that the return rate was significantly decreased [81], and the customers were willing to spend more [59]. Research has indicated that the adoption of virtual try-on technology for online apparel shopping can significantly reduce the risk regarding apparel fit perceived by consumers when shopping online while also increasing the enjoyment of the shopping experience [99].…”
Section: F Impact On Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the rapidly emerging works, there lacks a systematic survey to summarize image-based virtual tryon methods in datasets, method design and experimental evaluation. Two previous reviews [51], [52] only introduced several representative methods, but did not perform comprehensive comparison and unified evaluation. To the best of our knowledge, this is the first systematic image-based virtual try-on review with unified evaluation, which also has the following unique characteristics:…”
Section: Introductionmentioning
confidence: 99%